2013
DOI: 10.3174/ajnr.a3448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Image Noise on Image Quality and Quantitative Interpretation in Brain CT Perfusion

Abstract: BACKGROUND AND PURPOSE There is a desire within many institutions to reduce the radiation dose in CTP examinations. The purpose of this study was to simulate dose reduction through the addition of noise in brain CT perfusion examinations and to determine the subsequent effects on quality and quantitative interpretation. MATERIALS AND METHODS A total of 22 consecutive reference CTP scans were identified from an institutional review board–approved prospective clinical trial, all performed at 80 keV and 190 mAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Those authors found, however, that the CBV values of gray matter actually were underestimated by 18.6% in all patients, and the CBV values of white matter were overestimated by 1.5% with filtered back projection as the reconstruction algorithm, but they gave no explanation for this observation. Our optimal point of dose reduction was lower than the reduction of 33% (from 190 mAs to 125 mAs, no effective dose values were reported) suggested by Juluru et al (22). These authors found little effect of lower dose settings on perfusion values, although in their study, Juluru et al investigated five dose settings with simulated noise, whereas we used real measured noise.…”
Section: Neuroradiology: Quantitative Dose Dependency Analysis Of Whomentioning
confidence: 60%
See 1 more Smart Citation
“…Those authors found, however, that the CBV values of gray matter actually were underestimated by 18.6% in all patients, and the CBV values of white matter were overestimated by 1.5% with filtered back projection as the reconstruction algorithm, but they gave no explanation for this observation. Our optimal point of dose reduction was lower than the reduction of 33% (from 190 mAs to 125 mAs, no effective dose values were reported) suggested by Juluru et al (22). These authors found little effect of lower dose settings on perfusion values, although in their study, Juluru et al investigated five dose settings with simulated noise, whereas we used real measured noise.…”
Section: Neuroradiology: Quantitative Dose Dependency Analysis Of Whomentioning
confidence: 60%
“…To our knowledge, previously published work is limited primarily because of the difficulty of realistic simulation of patient data at different dose levels. In other studies, this was achieved by simply adding Gaussian noise (22), by reconstructing only a part of the total number of raw projections (21), or by using dual-source CT scanners and letting the two tubes operate at different milliampere and kilovolt settings simultaneously during acquisition (23). An alternative to our approach would be to use dedicated low-dose simulators (24,25).…”
Section: Neuroradiology: Quantitative Dose Dependency Analysis Of Whomentioning
confidence: 99%
“…Radiation dose varies linearly with mAs: a reduction to 40 % of the original mAs levels results in 40 % of the original radiation dose but also in higher image noise. The effect of lowered mAs was studied previously using a very simple noise simulation technique, which assumed that the addition of a fixed amount of noise is sufficient for reduced dose simulation regardless of patient size [11]. Recent studies, however, pointed out that the noise level of CT images varies depending on patient size at each slice as well as on the relative location within each slice.…”
Section: Introductionmentioning
confidence: 97%
“…To avoid the unethical repetitive scanning of the same patient at different radiation doses, we follow the practice in [23], [24] to simulate low-dose CT scan by adding spatially correlated statistical noise to the reconstructed CT images (before deconvolution). The tube current-exposure time product (mAs) varies linearly with the radiation dosage level.…”
Section: Methodsmentioning
confidence: 99%